시지각 프로그램이 경직성 뇌성마비 아동의 글씨 쓰기 명료도와 시지각 능력에 미치는 영향 - 김은혜; Eun Hye Kim; 배민정; Min Jung Bae; 전현용; Hyun Yong Jun; 장철; Chel Jang; 송민옥; Min Ok Song (Journal of the Korean Society of Integrative Medicine, 2015)
Purpose: This study intends to investigate if visual perception training program has influence on writing intelligibility and visual perception ability of the children who have spastic cerebral palsy. Methods: The subjects were 12 children of 4-8 years old. Classifying them into 2 groups - cerebral palsy children group(6) and normal children group(6), visual perception training program was conducted to the cerebral palsy children group twice a week for 4 weeks. Korean alphabet writing test and Korean-version development test on visual perception(DTVP-2) were used for the test. Result: First, the cerebral palsy children group had significantly lower scores on visual perception than the normal children group. Second, Two groups didn`t show significantly difference between before and after the visual perception training program. Third, The normal children group significantly increased at three parts without the visual perception training program. Forth, The cerebral palsy children group significantly increased at the only a part after the visual perception training program Conclusion: For the visual perception ability improvement of cerebral palsy children, it is necessary to systematic and continued intervention. And the study about the effect of the visual perception training program application according to by type characteristic of the cerebral palsy child wishes to proceed.